20 Egyptian songs to learn and sing : an easy way to learn Egyptian colloquial Arabic - Ossama, Bahaa Ed-Din; Grafen, Tessa (The American University in Cairo Press, 2021)
Songs are a great way to learn a language, and popular songs can reveal much about the culture and traditions of a country where the language is spoken. 20 Egyptian Songs to Learn and Sing brings together twenty songs performed by popular Egyptian singers, from iconic twentieth-century diva Umm Kulthum to present-day singing sensation Amr Diab. Following on the success of Kilma Hilwa: Egyptian Arabic through Popular Songs: Intermediate Level and Musiqa al-Kalimat: Modern Standard Arabic through Popular Songs: Intermediate to Advanced (AUC Press, 2015 and 2017), Bahaa Ed-Din Ossama and Tessa Grafen build a lively variety of language lessons around each song, accompanying them with notes on vocabulary, grammar and usage, and exercises. Aimed at beginner learners of Egyptian Colloquial Arabic and fans of Arab popular music, 20 Egyptian Songs to Learn and Sing is a motivational and highly enjoyable approach to learning Egyptian Arabic. Suitable for use in the classroom or for self-study. Includes songs by: Dina El Wedidi, Amr Diab, Sayed Darwish, Shadia, Mohamed Monir, Umm Kulthum, Suad Hosni, Nancy Agram, Dalida, and Rema Kheshesh.